2022
DOI: 10.1093/pnasnexus/pgab004
|View full text |Cite
|
Sign up to set email alerts
|

Can vaccine prioritization reduce disparities in COVID-19 burden for historically marginalized populations?

Abstract: SARS-CoV-2 vaccination strategies were designed to reduce COVID-19 mortality, morbidity, and health inequities. To assess the impact of vaccination strategies on disparities in COVID-19 burden among historically marginalized populations (HMPs), e.g. Black race and Hispanic ethnicity, we used an agent-based simulation model, populated with census-tract data from North Carolina. We projected COVID-19 deaths, hospitalizations, and cases from 2020 July 1 to 2021 December 31, and estimated racial/ethnic disparities… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Unlike many other existing COVID-19 ABMs (e.g. Hinch et al, 2021 ; Kerr et al, 2021 ; Krivorotko et al, 2022 ; Nguyen et al, 2021 ; Rosenstrom et al, 2022 ; Shamil et al, 2021 ; Silva et al, 2020 ), SIDD-NC is initialized with ten million agents and produces a health record for each agent for the entirety of the simulation time. Although it has higher computing power requirements, this in turn requires much less extrapolation of results to the study population, as the study population is represented 1:1 in the synthetic population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike many other existing COVID-19 ABMs (e.g. Hinch et al, 2021 ; Kerr et al, 2021 ; Krivorotko et al, 2022 ; Nguyen et al, 2021 ; Rosenstrom et al, 2022 ; Shamil et al, 2021 ; Silva et al, 2020 ), SIDD-NC is initialized with ten million agents and produces a health record for each agent for the entirety of the simulation time. Although it has higher computing power requirements, this in turn requires much less extrapolation of results to the study population, as the study population is represented 1:1 in the synthetic population.…”
Section: Discussionmentioning
confidence: 99%
“…Other COVID-19 specific ABMs have been created, largely emphasizing forecasting and parsimony (e.g. Hinch et al, 2021 ; Kerr et al, 2021 ; Krivorotko et al, 2022 ; Nguyen et al, 2021 ; Rosenstrom et al, 2022 ; Shamil et al, 2021 ; Silva et al, 2020 ; Yin et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…5 Because many communities at disproportionate risk for COVID-19 face barriers to vaccine access and uptake, it is essential for vaccine equity strategies to include community engagement efforts that facilitate trust, provide accurate and interpretable information, and respond to the needs and values of different community groups. 6,7 For example, Gonzalez and colleagues 8 improved vaccination rates through a community outreach program using a call/recall system that addressed vaccine hesitancy and facilitated real-time vaccine scheduling among eligible Black and Hispanic adults.…”
Section: Background and Significancementioning
confidence: 99%
“…essential worker status), which takes workplace-related risk differentials into consideration, improves outcomes relative to age-only prioritization. 10-19 Four studies found that it is optimal to switch to a focus on vaccinating the youngest/lowest-risk once most of the oldest/highest-risk people have been vaccinated. 15,20-22 Once the majority of the vulnerable are protected, there is a relatively larger benefit to slowing transmission by vaccinating high-contact groups.…”
Section: Introductionmentioning
confidence: 99%